Effect of Self Therapy - Helps Groups Against Family Coping With Mental Retardation Children In SLB - C Purbalingga - Ruti Wiyati; Welas Haryati; Dyah Wahyuningsih (Poltekkes Kemenkes Semarang, 2012)
The design of this study is a